Inferno's shadow - Anderson, Taylor, 1963- (Anderson, Taylor, 1963- Artillerymen series, 2025)
"Lost in a mysterious world, far from all they knew in 1847 America, Colonel Lewis Cayce and his soldiers must face the unimaginable might of the Dominion once and for all in this gripping alternate history from the New York Times bestselling author of the Destroyermen series. Colonel Lewis Cayce and his forces were a group of American soldiers bound to fight in the Mexican-American War-until they were stranded in a strange new world inhabited by strange monsters, new friends, and deadly foes. Now Cayce has brought his army of displaced Americans and their indigenous allies into the heart of the loathsome, blood-drenched Dominion's stronghold. If he can take the enemy's holiest city and support the elevation of a new "Supreme Holiness" who seeks to moderate the Dominion's thirst for expansion, slavery, and blood sacrifice, Cayce's own goal for his army and new people to live in security and freedom will be assured. But no matter how good of a soldier he is, Cayce is ruled by reason, and the madness and seemingly suicidal treachery of his adversaries, not to mention the sheer titanic scope of the force arrayed against him, might finally be more than he can cope with. Which side will ultimately discover that even victory can end in defeat?"--